The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.bpj.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin/Lipid Hydrophobic Matching—Rhodopsin Oligomerization and Function

Abstract: Lipid composition of the membrane and rhodopsin packing density strongly modulate the early steps of the visual response of photoreceptor membranes. In this study, lipid-order and bovine rhodopsin function in proteoliposomes composed of the sn-1 chain perdeuterated lipids 14:0d27-14:1-PC, 16:0d31-16:1-PC, 18:0d35-18:1-PC, or 20:0d39-20:1-PC at rhodopsin/lipid molar ratios from 1:70 to 1:1000 (mol/mol) were investigated. Clear evidence for matching of hydrophobic regions on rhodopsin transmembrane helices and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 40 publications
2
39
1
Order By: Relevance
“…A molecular-level understanding of the forces acting on lipids and proteins in membranes rests on knowledge of pure bilayer dynamics and thermodynamics in the absence of complicating protein molecules. For example, nuclear magnetic resonance (NMR) spectroscopy provides knowledge of average structure (142) and lipid mobility (27,95), and has been applied to investigate the influences of ions (25,141), water (84), cholesterol (1,26,106,114,161), and proteins (15,152). Segmental order parameters of the lipids are directly accessible (95), as interpreted by Seelig (142) and others (44,128) in terms of local bilayer structure and dynamics (27).…”
Section: Soft Matter and Membrane Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…A molecular-level understanding of the forces acting on lipids and proteins in membranes rests on knowledge of pure bilayer dynamics and thermodynamics in the absence of complicating protein molecules. For example, nuclear magnetic resonance (NMR) spectroscopy provides knowledge of average structure (142) and lipid mobility (27,95), and has been applied to investigate the influences of ions (25,141), water (84), cholesterol (1,26,106,114,161), and proteins (15,152). Segmental order parameters of the lipids are directly accessible (95), as interpreted by Seelig (142) and others (44,128) in terms of local bilayer structure and dynamics (27).…”
Section: Soft Matter and Membrane Functionmentioning
confidence: 99%
“…Experimental support comes from studies of the effects of the lipid acyl length on protein activity for Ca 2+ -ATPase (92) and rhodopsin (19,20,153). In the case of rhodopsin (19,20,152), the MI-MII activation equilibrium depends on the lipid acyl-chain length, where a thicker bilayer (128) favors the active MII state (see Figure 1). That leads us to the idea that the equilibrium can be tipped toward one state or the other, depending on structural features such as the bilayer thickness matching.…”
Section: Hydrophobic Matching and Bilayer Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the structural and dynamical properties of biomembranes are mediated by the lipid composition and interactions with the proteins, water, cholesterol, and surfactants (Brown and Chan, 2007; Coskun and Simons, 2011; Kaiser et al, 2009; Kaye et al, 2011; Kinnun et al, 2015; Leftin et al, 2014b; Mallikarjunaiah et al, 2011; Rheinstädter et al, 2004; Tyler et al, 2015). Membrane remodeling requires mesoscopic elastic deformations of the lipids (Kinnun et al, 2015) that can play a central role in biological functioning with regard to lipid-protein interactions, domain formation, and various nano- and microstructures implicated in key cellular functions (Brown, 1997; Brown, 2012; Liang et al, 2014; Soubias et al, 2014, 2015; Teague et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The TM region must influence the functions of membrane proteins by rotation, association, or changing its orientation and even its secondary structure. Increasing evidence has suggested that the characteristics of the membrane, which is composed of numerous lipid molecules, considerably influences membrane protein function . Therefore, molecular characterization of the TM region within the lipid bilayer is essential to understand the molecular mechanisms that regulate the functions of membrane proteins.…”
Section: Introductionmentioning
confidence: 99%